Diversidad y abundancia de especies dulceacuicolas en el estero maculillo, canton Mocache - Rivas Ibarra, Feraul Adrian (2022)
The study was carried out in the Maculillo estuary belonging to the Mocache canton, with the objective of knowing the diversity and abundance of freshwater fish present, since unfortunately changes have been observed in the hydrography of the environment that affect and decimate the production of said native species, due to to loss of habitat due to the physical alteration of rivers, deforestation, degradation of wetlands and floodplains, water pollution from agricultural and urban activities, mining, oil exploitation, dams, overfishing, invasive species and climate change, there are no previous local studies about this aquaculture resource; Artisanal fishing was carried out on different dates during the months of August until September 2022, taking 4 sampling points as a reference. For the collection of the fish, a 10m trammel net with a 2.5-inch eye was used, the abundance and diversity were recorded, these records were used for the results: for abundance, a total of 54 individuals collected belonging to three orders ( Characiformes, Siluriformes and Cichigormes). The Characiformes order being the richest of families, which share this habitat and are endemic to the area. The fish with the greatest presence was the dica, 12 specimens were collected representing 22.2% abundance followed by ladies with 18.5% followed by Mouse with 14.81% respectively. For Biomass in each family the best values of 1428.00g., in the species Brycon alburnus, common name dama. Tracked for the collected species Leporinus ecuadorensis, Mouse with 1034g. It is concluded that the richness of abundance and diversity of the species collected under study is rather low, it could be due to the fishing season that affected the results. Keywords: endemic, sustainability, pollution, artisanal fishing, extinction